2008
DOI: 10.1111/j.1365-2702.2008.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the early discharge experiences of stroke survivors and their carers

Abstract: An improved understanding of the issues facing stroke patients and carers during their early days at home should facilitate the preparation for discharge in the hospital setting and allow more focussed follow-up services in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 70 publications
(194 reference statements)
1
29
0
Order By: Relevance
“…Although several literature reviews (i.e., CarodArtal & Egido, 2009;Pringle, Hendry, & McLafferty, 2008;Vanhook, 2009) were identified that assessed caregivers of stroke survivors, none were found that specifically addressed the interaction between psychological stressors and physical health of family caregivers. The purpose of this review was to identify the way in which variables are operationalized in studies addressing psychological stressors and physical health of family caregivers of stroke survivors.…”
Section: Introductionmentioning
confidence: 98%
“…Although several literature reviews (i.e., CarodArtal & Egido, 2009;Pringle, Hendry, & McLafferty, 2008;Vanhook, 2009) were identified that assessed caregivers of stroke survivors, none were found that specifically addressed the interaction between psychological stressors and physical health of family caregivers. The purpose of this review was to identify the way in which variables are operationalized in studies addressing psychological stressors and physical health of family caregivers of stroke survivors.…”
Section: Introductionmentioning
confidence: 98%
“…A systematic literature review of studies on stroke patients' early discharge experiences revealed that the process of change and disruption of life becomes more obvious for patients once they return home [16]. These authors specifically emphasised the need to explore in greater depth patients' experiences in the context of early discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of stroke on informal caregivers is also gradually being recognized. 12 The burden on the carer and families that can come with early discharge of the stroke survivors from the hospital can have deleterious effects on their health, which then negatively affect the recovery of the stroke patient.…”
Section: Why Is Community Rehabilitation For Stroke Survivors Important?mentioning
confidence: 99%
“…Some services, such as ESD, have been shown to be only beneficial for survivors of mild to moderate stroke (initial Barthel Index of [10][11][12][13][14][15][16][17][18][19][20]. 18 This means that those who experienced a very mild or more severe stroke (<10 Barthel Index) require alternative service provision when they leave the hospital.…”
Section: Time and Length Of Interventionmentioning
confidence: 99%